A Study on Risk Exchange and Allocation from the Network Perspective - Wei, Wang; Ming, Liu (Advances in Social Sciences Research Journal, 2023)
This paper establishes a network model to study the risk exchange and allocation process. The risk units in the model determine whether they exchange risk with other units according to the criterion of expected variance. For simplicity, risk is given in terms of income. The article finds that individuals (nodes) with higher volatility will obtain higher exchange value in risk exchange; under the condition of constant income, if this process is repeated many times, then the value of the entire risk exchange network will be Produces an effect similar to a risk pool, with high-volatility risk nodes obtaining the largest average share of revenue. These results may be applied in the development of various risk matching and mutual aid programs.